Cloud based smart route system for blinds - Nijhum, Mushfikunnabi; Alam, Tasnim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.